The Impact of Work-Life Balance Policies on Employee Job Satisfaction in Wuling Factory, Shanghai - Yuan, Zhang; Suryani, Embun (Asian Journal of Management Analytics, 2025)
The automotive industry is a high-pressure sector where work-life balance (WLB) is crucial to employee job satisfaction and productivity, particularly in demanding contexts such as Wuling Factory in Shanghai. This research examines the efficacy of WLB policies at Wuling Factory and their impact on job satisfaction. Utilizing a quantitative research method, a structured questionnaire was distributed among 200 employees, and Structural Equation Modeling (SEM) was applied to analyze the data. The findings indicate that flexible working hours, specialized leave options, and dependents care significantly enhance job satisfaction. This study not only underscores the importance of WLB in industrial work environments but also contributes to the broader discourse on human resource management by demonstrating that comprehensive, well-implemented WLB policies are integral to fostering employee satisfaction and organizational success in the automotive manufacturing industry.